Multilateral Diplomacy as China’s Expansionism in ACFTA - Maria Indira Aryani; Rista Vauza Wardania; Widji Anugrah Sari (WIMAYA, 2020)
ACFTA or ASEAN-China Free Trade Area, also known as China-ASEAN Free Trade Area is an economic agreement to construct a free trade zone between 10 ASEAN member countries and China to eliminate various tariff and non-tariff barriers. All of ASEAN members’ leaders and China’s leader signed the ACFTA on November 5, 2002 in Phnom Penh, Cambodia which latter came into effect on January 1, 2010. Since then, it was recorded in 2016 that the total trade between ASEAN and China has reached to US$ 475 billion, thus making China as ASEAN’s largest trading partner while ASEAN serves as China’s third largest trading partner. This means that China’s export to ASEAN is more than ASEAN’s export to China. It could be seen that the free trade area has benefitted China more than it has benefit ASEAN. This paper aims to provide brief explanation on how China is able to benefit more on the trade agreement. Using a descriptive method of analysis, combined with expansionism and multilateral diplomacy concepts, it can be found that China is able to utilize various means to maximize its benefit in the ACFTA scope of agreement. Through the ACFTA, China has managed to master trade routes, break trade barriers, invest more, deepen economic cooperation contracts and master production skills in manufacturing all across ASEAN member countries. All of these efforts are made possible by China’s favourable multilateral diplomacy instruments in the ACFTA.